Anesthetic Strategies in Cerebral Edema: Navigating Neurological Challenges Amid Trauma, Tumors and Therapeutic Advances - Świercz, Maciej; Markowiak, Szymon; Wardęszkiewicz, Marta; Jabłońska, Wiktoria; Kasprzak, Amelia; Truchta, Monika; Mańkowska, Aleksandra; Kolano, Agata; Pejas, Anna (Journal of Education, Health and Sport, 2024)
Cerebral edema, characterized by abnormal fluid accumulation in brain tissue leading to increased intracranial pressure, poses significant challenges for anesthesiologists. This review delves into the pathophysiology, clinical manifestations, diagnostic approaches, pharmacological strategies, and anesthesiological considerations associated with cerebral edema. Disruptions in the blood-brain barrier, alterations in cerebral blood flow, cellular swelling, and aquaporin dysregulation contribute to the complexity of cerebral edema. Clinical presentations vary, encompassing cognitive changes, seizures, and neurological deficits. Accurate diagnosis relies on clinical assessments and neuroimaging, with MRI and CT scans playing pivotal roles. Pharmacological interventions, including osmotic agents, corticosteroids, diuretics, and barbiturates, target specific causes and symptoms. Anesthesiological challenges encompass ICP monitoring, choice of anesthetic agents, maintenance of cerebral perfusion, fluid management, temperature control, and collaboration with neurosurgical teams. This multidisciplinary approach ensures optimal patient care and emphasizes ongoing research collaboration for refining therapeutic strategies. This comprehensive review provides valuable insights for clinicians managing cerebral edema, offering a roadmap for tailored interventions and highlighting the need for continued advancements in understanding and treating this critical condition. Material and method: ​​ The literature review applied standard criteria and focused on PubMed articles using keywords: cerebral edema, pathophysiology, aquaporin, blood-brain barrier, anesthesiology, cerebral edema treatment, corticosteroids